Touriboost: tourism experiences through hidden cultural heritage stories - Çınar, Kevser (Necmettin Erbakan Üniversitesi, 2021)
Cultural heritage helps us explore and understand what life was like for people through the ages. Their societies, settlements, crafts and entertainment, their agriculture, trade, their health and their warfare. This book (and ibooks through the QR codes inside the book) created as an output of a Project funded by the Erasmus+ Programme of the European Union in order to bring some of the fascinating cultural heritage stories to light. Throughout the book you will explore the stories of past landscapes and environments, urban planning and architecture, trade and migration, power and identity, and religion and daily life practices that are preserved across Turkey and Europe.